Herbivore-derived fatty-acid amides elicit reactive oxygen species burst in plants. (28th December 2017) - Block, Anna; Christensen, Shawn A; Hunter, Charles T; Alborn, Hans T
Abstract : Fatty-acid amides from lepidopteran pests elicit a reactive oxygen species burst in plants partially mediated by NADPH oxidases, yet an Arabidopsis NADPH oxidase double mutant displays enhanced insect resistance. Abstract: Reactive oxygen species (ROS) can be elicited by many forms of stress, including pathogen attack, abiotic stress, damage and insect infestation. Perception of microbe- or damage-associated elicitors triggers an ROS burst in many plant species; however, the impact of herbivore fatty-acid amides on ROS elicitation remains largely unexplored. In this study we show that the lepidopteran-derived fatty-acid amide elicitor N -linolenoyl-L-glutamine (GLN18:3) can induce a ROS burst in multiple plant species. Furthermore, in Arabidopsis this ROS burst is partially dependent on the plasma membrane localized NADPH oxidases RBOHD and RBOHF, and an Arabidopsis rbohD / F double mutant produces enhanced GLN18:3-induced jasmonic acid. Quantification of GLN18:3-induced ROS in phytohormone-deficient lines revealed that in Arabidopsis reduced levels of jasmonic acid resulted in a larger elicitor-induced ROS burst, while in tomato reduction of either jasmonic acid or salicylic acid led to higher induced ROS production. These data indicate that GLN18:3-induced ROS is antagonistic to jasmonic acid production in these species. In biological assays, rbohD / F mutant plants were more resistant to the generalist herbivores Spodoptera exigua and Trichoplusia ni but not to the specialist Plutella xylostella . Collectively, these results demonstrate that in Arabidopsis herbivore-induced ROS may negatively regulate plant defense responses to herbivory.